Effects of Different Intensities of Weighted Vest Warming up Session on Physical Performances of Power Sports Athletes - Ab Malik, Zulezwan; Ishak, Asmadi; Aiwa Rosman, Noor; Osman, Noorzaliza; Kadir Mahmod, Abdul; Oliver Francis, Leo; Md Nadzalan, Ali (International Journal of Engineering and Technology, 2018)
Optimum physical performance is vital component for athletes to excellent in their sports. Weighted vest warming up is one of the ways to manipulate intensities of warming. The purpose of this was to investigate the effect of different intensities weighted vest warming up session on physical performances. Twenty participants from power sports athletes was did all weighted vest warming up protocol (a) wore weighted vest 6% of body mass,(W6),(b) wore weighted vest 12% of body mass (W12)Â (c) with body weight only or 0% of additional weight in intensities of warming up session (W0). All participants undergo cross over design and evaluated using vertical jump test, standing broad jump test, seated medicine ball toss test and 20m sprint test after finish each warming up sessions. 1-way, repeated-measures analysis of variance on the test result showed significant different of the effect different intensities of weighted vest warming up session on all physical performances test. In conclusion, usage of 6% and 12 % from body weight of additional weight on weighted vest warming up session can promote to improving physical performances.Â Â